Impact of estrogen replacement therapy on outcomes following total shoulder arthroplasty: a propensity-matched retrospective cohort study of 1,779 patients - Seyedeh Zahra Mousavi, BS; Ethan R. Harris, BS; Sanjana Agarwal, BS; Prasenjit Saha, BA; Eve R. Glenn, ScB; Henry M. Fox, MD; Umasuthan Srikumaran, MD, MBA, MPH (JSES International)
Background: While estrogen is essential for bone remodeling, its impact on joint health is more nuanced. Previous studies suggest that high estrogen states, including those induced by estrogen replacement therapy (ERT), are associated with osteoarthritis and an increased risk of revisions after hip and/or knee arthroplasty. Given the rise in total shoulder arthroplasty (TSA) cases, it is important to investigate factors that may impact its outcomes. This study aimed to evaluate whether ERT use impacts TSA outcomes at 2, 4, and 10 years postoperatively. Materials and methods: This was a retrospective cohort study of females aged ≥55 years who underwent TSA, using the TriNetX Research Network. Patients were stratified by ERT use for at least 1-5 years preoperatively. One-to-one propensity score matching was performed based on age, race, bone density, osteoarthritis, and other comorbidities. Primary outcomes were revision rates at 2, 4, and 10 years. Secondary outcomes included prosthetic joint infections, mechanical complications, and shoulder instability, as well as 90-day postoperative medical complications. Tests of significance and risk ratios (RR) were calculated to compare outcomes with an alpha of <0.05. Results: After matching, 1,779 patients were included in each group. At 90 days, the ERT cohort had a higher risk of deep vein thrombosis (RR =1.91; P = .012). At 2 and 4 years postoperatively, the ERT group had a significantly higher risk of revisions (RR = 1.71 and 1.59, respectively), shoulder instability (RR = 1.81 and 1.80), and overall mechanical complications (RR = 1.60 and 1.67). At 10 years, the risk for revisions (RR = 1.59; P = .002) and mechanical complications (RR = 1.43; P = .005) persisted. Conclusion: Our findings suggest that ERT is associated with long-term increased risk of revision procedures and mechanical complications following TSA. This demonstrates the complex relationship between estrogen and bone health, highlighting the need for future studies investigating the impact of ERT on implant survival and osseointegration.